LEADERSHIP, INNOVATION AND ENGAGEMENT IN QUALITY IMPROVEMENT IN THE AMBULANCE SERVICES CARDIOVASCULAR QUALITY INITIATIVE: CROSS SECTIONAL STUDY. Issue 5 (18th April 2015) - Essam, Nadya; Phung, Viet-Hai; Asghar, Zahid; Spaight, Anne; Siriwardena, Aloysius Niroshan
Abstract : Introduction: Clinical leadership and organisational culture are important contextual factors for successful Quality Improvement (QI) programmes. The relationship between these and with organisational performance is complex and poorly understood. We aimed to explore the relationship between leadership, culture of innovation, and clinical engagement in QI for organisations participating in a large-scale national ambulance Quality Improvement Collaborative (QIC). Methods: We used a cross sectional survey design. An online questionnaire was distributed to 22, 117 frontline ambulance staff across all 12 ambulance services in England. Scores (0–100%) were derived for each key aspect: clinical leadership; culture of innovation; use of QI methods; and effectiveness of QI methods. Responses to an open-ended question were analysed and complemented the quantitative findings. Results: There were 2, 743 (12%) responses from 11 of 12 participating ambulance services. Despite only a small proportion of responders (3%) being directly involved with ASCQI, leadership behaviour was significantly higher for ASCQI members than for non-ASCQI members. Involvement in ASCQI was not significantly associated with responders' perceptions of the culture of innovation of their organisation, which was generally considered to be poor. ASCQI members were significantly more likely to use QI methods but overall uptake of QI methods was low. The use of QI methods was also significantly associated with leadership behaviour and service tenure. Limitations: There was a low response rate, although sufficient responses to enable comparison of those who participated in ASCQI with those who did not. Conclusion and recommendations: Although participants reported a lack of organisational culture of innovation, considered a prerequisite for QI, the collaborative achieved significant wide-scale improvements in prehospital care for myocardial infarction and stroke. We postulate that improvement was mediated through a 'QI subculture' developed from ASCQI's distributed leadership and network. Further research is needed to understand success factors for QI in different complex healthcare environments.